Investasi Generasi Muda Dalam Surat Berharga Negara Ritel Sebagai Wujud Bela Negara - Muljanto, Muhammad Agus (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
State defense is the right and obligation of every citizen to be carried out both physically and non-physically. The development of various government infrastructure is inseparable from financing constraints in the APBN in the form of a financial gap that can be overcome, among others, by foreign loans which have the consequence of increasing the burden on the APBN every year if there is a depreciation of the Indonesian currency against the foreign currency used. In addition, the choice of strategy through portfolio investment by foreign investors through the purchase of SBN carries a risk that massive selling of SBN in the secondary market can lower the price of SBN and have an impact on the credibility of the government. As an alternative solution, it is necessary to intensify the deepening and inclusion of the domestic financial market as a manifestation of defending the country, especially the contribution of the younger generation in national development through the purchase of retail SBN. However, the challenge faced is the low level of public financial literacy to increase the domestic investor base in retail SBN ownership. The method in this research is to conduct an assessment of the concepts and theories used based on the availability of literature from scientific journal articles, books, and regulations. The results of the analysis show retail investors as the targeted target considering the proportion of the younger generation population is increasing and the character of Indonesian retail investors is generally buy and hold, which is different from the behavior of foreign investors who tend to be profit oriented. Ownership of retail state securities in addition to obtaining a fixed return in the form of a coupon that remains until maturity also has pride as an embodiment of defending the country and love for the homeland has invested in national development. Increasing the younger generation in retail SBN ownership means strengthening the domestic investor base and strengthening the resilience of the nation's and state's economy.Keywords: National Defense, Young Generation, Retail SBN Abstraksi-Bela negara merupakan hak dan kewajiban setiap warga negara untuk dilakukan baik secara fisik maupun nonfisik. Pembangunan berbagai infrastruktur pemerintah tidak terlepas dari kendala pembiayaan dalam APBN  berupa financial gap yang dapat ditanggulangi antara lain dengan pinjaman luar negeri yang memiliki konsekuensi menambah beban APBN setiap tahunnya bilamana terjadi depresiasi mata uang Indonesia terhadap mata uang asing yang dipergunakan. Disamping itu pilihan strategi melalui investasi portofolio oleh pemodal asing melalui pembelian SBN memiliki risiko dimana penjualan SBN secara masif di pasar sekunder dapat menurunkan harga SBN dan berdampak terhadap kredibilitas pemerintah. Sebagai alternatif solusi perlu digiatkan pendalaman dan inklusi pasar keuangan domestik sebagai perwujudan bela negara khususnya kontribusi generasi muda dalam pembangunan nasional melalui pembelian SBN ritel. Namun tantangan yang dihadapi yaitu literasi keuangan masyarakat yang masih rendah untuk meningkatkan basis investor domestik dalam kepemilikan SBN ritel. Metode dalam penelitian ini dengan melakukan pengkajian mengenai konsep dan teori yang digunakan berdasarkan pada ketersediaan literatur baik dari artikel jurnal ilmiah, buku, dan peraturan. Hasil analisis menunjukkan investor ritel sebagai target yang dibidik mengingat populasi generasi muda semakin bertambah proporsinya dan karakter investor ritel Indonesia umumnya buy and hold, yang berbeda dari perilaku investor asing yang cenderung profit oriented. Kepemilikan surat berharga negara ritel disamping memperoleh pengembalian tetap berupa kupon yang tetap sampai jatuh tempo juga memiliki kebanggaan sebagai perwujudan bela negara dan cinta tanah air telah berinvestasi dalam pembangunan nasional. Peningkatan generasi muda dalam kepemilikan SBN ritel berarti turut memperkuat basis investor domestik dan memperkuat ketahanan perekonomian bangsa dan negara.